Dielectric properties of lead-free solid solution of Bi 0.487Na0.487La0.017TiO3 and BaTiO3 - Nuttapon Pisitpipathsin (2018)
Bismuth sodium titanate (Bi0.5Na0.5TiO3; BNT) is one of the most preferred materials for the preparation of lead-free ceramics; however its dielectric property is lower than that of lead-based materials. Thus, the substitution of A and B-site cations is considered to be one of the best solutions in order to improve both the dielectric and piezoelectric properties. In this study, lead-free ceramics from bismuth sodium lanthanum titanate (Bi0.487Na0.487La0.017TiO3; BNLT) and barium titanate (BaTiO3; BT) systems were prepared by a modified two-step mixed oxide method. BT powder was added to BNLT powder with the desired compositions of (1 - x)BNLT-xBT, where x = 0.00, 0.02, 0.04, 0.06, 0.08, and 0.10. It was found that the addition of BT in the BNLT improved the electrical properties of ceramics. Phase transition of rhombohedral to tetragonal structure was significantly dependent on the amount of BT added. It was also found that the change in crystal structure affected the ferroelectric property of the ceramics where the transition from ferroelectric to antiferroelectric started from the samples with x≥ 0.06 mol% and higher. This may be useful in terms of using these materials in the desired applications. © 2010 Taylor & Francis.